THEFT OF CASH FROM ATMS (QUALIFICATION ISSUES) - Лихова, Софія Яківна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: it is substantiated that when qualifying the theft of money from an ATM with the use of someone else’s bank card, the person should be charged with such a qualifier as penetration. The methodological basis of the study was general scientific methods of cognition, with which the author creates the basic principles of qualification of crimes on the basis of penetration. Results: the author emphasizes the need to review the practice of courts on the use of qualifying features of theft and, in particular, such a feature as penetration. Discussion: the article considers specific court decisions on the qualification of theft from an ATM with the help of a stolen payment card, in which courts ambiguously use the qualifying sign of «penetration». It is necessary to understand the essence of theft with the use of a stolen payment card. Of course, it is clear that by stealing the card, the guilty person is already, practically, taking possession of the money that is on it. If the cardholder does not block it in time, his money will be stolen from his account and the bank in this case is not even obliged to reimburse this amount. But we believe that such actions should still be classified as burglary. In fact, the theft of a payment card in itself qualifies as an attempt to commit a crime - theft. The criminal only has to get into the safe - the ATM. What he does with a special tool - someone else’s payment card. The illegality of transactions with other people’s bank cards is obvious. Today, when under Ukrainian law theft without aggravating circumstances is not considered a crime but a misdemeanor and the punishment for this act does not entail even a criminal record, the responsibility for one of the most common crimes against another’s property - for theft - should be strengthened. After all, if the offender stole the keys and then broke into someone else’s apartment, there is no doubt that the act is qualified on the basis of breaking into a home or premises. Keys are a means of penetration, just like a stolen payment card.